Changing Vectors of International Cooperation of Russian Universities in the New Geopolitical Situation - Larisa V. Konstantinova; Ekaterina S. Titova; Anton M. Petrov; Zulfiya A. Troska; Olga D. Nikonova (National Research Mordova State University, 2023)
Introduction. With the implementation of state policy aimed at integrating the Russian higher education into the world educational system, universities internationalization has been intensively developing in recent decades. However, the unprecedented sanction pressure of unfriendly countries (starting in 2022) affected universities international activity prompting them to search for new foreign partners. The purpose of the research was to study the vectors of Russian universities' international activity under transformation in the current geopolitical situation. The analysis of new geography and forms of international cooperation in the educational, scientific, cultural and humanitarian spheres was of specific interest. Materials and Methods. The method of content analysis was employed to study the news on international activity, posted on the websites of leading Russian universities, government authorities and specialized organizations. The results of this analysis were mapped (the mapping method was used). The method of substantive analysis of news reports was used to obtain a characterization of the forms of international cooperation. Statistical data were analyzed in the article by means of quantitative methods. The methods of substantive analysis, systematization and classification of information contained in theoretical sources, normative-legal acts, information and analytical materials were used. Results. A set of sanction restrictions on the internationalization of Russian universities is characterized. Diagrammatic maps of the new geography of their international cooperation are presented. They indicate the growth of international contacts with universities in the CIS countries, Asia, Africa and Latin America against the backdrop of the decreased contacts with Western countries. Discussion and Conclusion. The expansion of international cooperation between Russian universities geography can help minimize risks of sanction pressure, as well as open up new opportunities for the long-term international partnership development and the formation of new world scientific and educational superiority centers. The article can be useful for universities in Russia for forming their international strategy in the new geopolitical conditions.